PENGARUH SET PELUANG INVESTASI TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Prasetyo, Adi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
The main objective of this research is to empirically examine the influence of investment opportunity set (IOS) to corporate social responsibility (CSR) disclosure. The variable of investment opportunity set (IOS) has broad alternatives, so the growth firms and non growth firms are used for measuring IOS. There are four indicators are used to determine growth firm and non growth firm. The indicators consist of: market-to-book assets, market-to-book equity, price-earning ratio, and the ratio of total capital expenditures to book total assets. The empirical results of the research show that IOS has significant influence on the disclosure of CSR. The result has been supported by the examine of distinguish of disclosure of CSR between growth firm and non growth firm.